Domestic and Foreign Investor Dynamics in Indonesian Stock Exchange : Evidence from 10 Years High-Frequency Data - Arroisi, Abdurrahman; Koesrindartoto, Deddy Priatmojo (The Indonesian Capital Market Review, 2019)
This study analyses price impact, herding behaviour, and feedback trading of domestic and foreign investors in Indonesia Stock Exchange (IDX) by employing vector autoregressive models using high-frequency transaction data in the period of 2008 – 2017. We find that domestic investors impact return negatively whereas foreign investors have no impact to return. In terms of herding behavior, domestic and foreign investors herd to themselves strongly. Domestic investors reverse-herd to foreign investors in the short-term (1 day) but no consistent pattern in the opposite direction. Regarding feedback trading, both domestic and foreign investors are contrarian in the big and medium cap portfolios but employ momentum strategy in the small cap portfolio. We also find that, in the crisis period, price impact is more pronounced in terms of economic and statistical significance. On the other hand, evidence of herding behavior and feedback trading decreases in market downturns, although with the same patterns overall.